Fluorescence correlation spectroscopy reveals the dynamics of kinesins interacting with organelles during microtubule-dependent transport in cells - de Rossi, María Cecilia (2019)
Microtubule-dependent motors usually work together to transport organelles through the crowded intracellular milieu. Thus, transport performance depends on how motors organize on the cargo. Unfortunately, the lack of methodologies capable of measuring this organization in cells determines that many aspects of the collective action of motors remain elusive. Here, we combined fluorescence fluctuations and single particle tracking techniques to address how kinesins organize on rod-like mitochondria moving along microtubules in cells. This methodology simultaneously provides mitochondria trajectories and EGFP-tagged kinesin-1 intensity at different mitochondrial positions with millisecond resolution. We show that kinesin exchange at the mitochondrion surface is within ~100 ms and depends on the organelle speed. During anterograde transport, the mitochondrial leading tip presents slower motor exchange in comparison to the rear tip. In contrast, retrograde mitochondria show similar exchange rates of kinesins at both tips. Numerical simulations provide theoretical support to these results and evidence that motors do not share the load equally during intracellular transport.